1979
DOI: 10.1021/ar50144a003
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of oxidized sulfur centers in organic sulfides. Radical cations and odd-electron sulfur-sulfur bonds

Abstract: If this interpretation is correct, the variable transition-state theory seems to be valid also for dehalogenation reactions. With meso-1,2-dibromo-1,2-diphenylethane as the substrate, the transition-state structure is central when the nucleophile is a halide ion and shifts toward the Elcb-like side with Ph3P. It is possible that with the latter base the incipient positive charge on the phosphorus atom in the transition state favors the buildup of negative charge a t Cg, thus promoting a transition state with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
190
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(202 citation statements)
references
References 19 publications
10
190
0
2
Order By: Relevance
“…It is known that radicals can undergo very fast intramolecular rearrangement reactions, particularly if structural and spatial conditions are favorable [26]. The tendency of the polarizable sulfur atom to participate in radical reactions has been known for decades in many fields of chemistry [27][28][29][30]. It has been demonstrated that electron attachment to a disulfide bond leads to significant bond weakening and formation of stable radical species at low temperature in solution [31,32].…”
Section: Gas-phase Scrambling Of Disulfide Bonds In Sel24kmentioning
confidence: 99%
“…It is known that radicals can undergo very fast intramolecular rearrangement reactions, particularly if structural and spatial conditions are favorable [26]. The tendency of the polarizable sulfur atom to participate in radical reactions has been known for decades in many fields of chemistry [27][28][29][30]. It has been demonstrated that electron attachment to a disulfide bond leads to significant bond weakening and formation of stable radical species at low temperature in solution [31,32].…”
Section: Gas-phase Scrambling Of Disulfide Bonds In Sel24kmentioning
confidence: 99%
“…Odd-electron bonding is of both fundamental and practical interest [8][9][10][11][12][13] . Three-electron s-bonding was first proposed by Linus Pauling in 1931 (ref.…”
mentioning
confidence: 99%
“…Thelong Co-Co bonds in 1C + , 2C + ,and anti-3C + may be rationalized by as imple three-electron bonding model as formed by the interaction of am ono-cobalt radical cation center with lone pair electrons of another cobalt atom, leading to ab ond order of 1/2 or less,a nalogues to threeelectron s-bonds ( Figure S10) of main group elements. [10,17,18] To the best of our knowledge, 2C…”
Section: Anti-3cmentioning
confidence: 99%